2022
DOI: 10.1155/2022/5244538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerosol Inhalation Combined with Intravenous Drip of Polymyxin B on Bacterial Clearance, Symptoms Improvement, and Serum Infection Indexes in Patients with Pneumonia Induced by Multidrug-Resistant Gram-Negative Bacteria

Abstract: In recent years, the incidence of pneumonia caused by multidrug-resistant (MDR) Gram-negative bacteria (G−) has increased year by year. Polymyxin B has a good clinical effect in the treatment of MDR, but there is controversy about the administration route of this drug. In this study, we retrospectively analyzed the clinical data of 84 cases of MDR Gram-negative bacterial pneumonia, and aimed to explore the effects of aerosol inhalation combined with intravenous polymyxin B infusion on the bacterial clearance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Due to differences in access to polymyxin B in various countries and regions, there are relatively few international studies on nebulized polymyxin B. Some studies have investigated nebulized polymyxin B as an adjunctive treatment with intravenous polymyxin B in VAP patients, and found that combination treatment can achieve better clinical efficacy ( Hasan et al, 2021 ; Zhou et al, 2021 ; Lin et al, 2022 ). We have searched the relevant literature, and there appears to be no clinical trial comparing the results of polymyxin B and polymyxin E nebulized therapy for VAP.…”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in access to polymyxin B in various countries and regions, there are relatively few international studies on nebulized polymyxin B. Some studies have investigated nebulized polymyxin B as an adjunctive treatment with intravenous polymyxin B in VAP patients, and found that combination treatment can achieve better clinical efficacy ( Hasan et al, 2021 ; Zhou et al, 2021 ; Lin et al, 2022 ). We have searched the relevant literature, and there appears to be no clinical trial comparing the results of polymyxin B and polymyxin E nebulized therapy for VAP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nebulized inhalation method can significantly increase the lung tissue concentration of polymyxin while decreasing the systemic exposure level of the drug, thus achieving the goal of improving the efficacy and reducing systemic adverse effects (Tang et al, 2023). Currently, several domestic and international guidelines and consensus recommend nebulized inhalation of polymyxin as one of the important therapeutic methods for multidrug-resistant gramnegative (MDR-GRN) bacterial induced pneumonia (Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%